History of the Supreme Court - Emrick, Eugene (My University, 1900)
Introduction: In writing a history of the Supreme Court of the United States, a few words concerning the courts of England, after which our system was modeled, may not be out of place. In England, the jurisdiction and powers of the courts are not so great as here, and it is a source of complexity to the English statesman why our Supreme Court does not control the legislative department. England has no written constitution. What is termed her constitution, is but a code of laws which are constantly changed from year to year, as new laws are passed and old ones are taken away. Parliament is supreme. It makes all laws, and can unmake them at any time. If an English court finds a law of Parliament conflicting with a decided case, the act will be observed as it is supposed to be the last expression of Parliament on that subject. If the court misinterprets an act, or decides it differently from what Parliament intended, the decision will stand until Parliament again meets and reenacts the law. Their courts do not have to decide between two conflicting statutes. They simply look up the date of their enactments, and that of the later date will be the one observed. What is the decision of the court one year, may not be the next, for the court follows the acts of Parliament and Parliament may, at any time, pass a law which conflicts with, and repeals the one, on which the court has based its decision. Such, in brief, is the plan which the English courts follow.
Citation: Emrick, Eugene. History of the Supreme Court. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: History; Supreme Court; English Courts; Theses